Cloning and expression of the complement fixation antigen-chitinase of Coccidioides immitis. - Zimmermann, C R (1996)
A chitinase had been isolated from the culture filtrates of Coccidioides immitis endosporulating spherules and from hyphae and shown to be the coccidioidal complement fixation (CF) and immunodiffusion-CF antigen. In the present study, we made use of our previously determined amino-terminal (N-terminal) sequence of the CF-chitinase to design degenerate oligonucleotide primers and to amplify and sequence a PCR product that coded for the N-terminal portion of the CF-chitinase. The PCR product was used as a hybridization probe to screen a developing spherule-(lambda)ZAP cDNA library, and three hybridizing clones were selected. These clones were converted into their pBluescript expression plasmid form in Escherichia coli and induced to express their recombinant proteins. Lysate from only one clone, pCTS 4-2A, yielded an enzymatically functional CF-chitinase and a line of identity with control immunodiffusion-CF-positive antigen. The pCTS 4-2A insert was sequenced and found to contain a deduced open reading frame coding for a 427-amino-acid polypeptide with an approximate molecular weight of 47 kDa. When purified by a chitin adsorption-desorption method, the recombinant protein exhibited virtually identical characteristics to those of the original C. immitis CF-chitinase. Nondenaturing gels of the pCTS 4-2A E. coli lysates and the purified C. immitis and recombinant CF-chitinase revealed proteins that had chitinase activity and similar relative electrophoretic mobilities. The appearance and relative levels of hybridizing RNA from the developing spherules-endospores (SEs) and hyphae correlated with the appearance or presence and level of CF-chitinase enzyme activity found in SEs culture filtrate and in cellular extracts of developing SE and hyphae. Thus, a functional recombinant CF-chitinase antigen was produced in E. coli and was used in serological diagnostic applications. These results also suggest a functional role for this chitinase in SE development and maturation.